2018
DOI: 10.1001/jamaoto.2018.2143
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fludeoxyglucose F 18–Labeled Positron Emission Tomography and Computed Tomography With the Detection of Oropharyngeal Cancer Recurrence

Abstract: The results indicate a higher specificity for FDG PET-CT for initial posttreatment surveillance imaging among patients treated with primary surgery compared with nonsurgical management. Both sets of patients with posttreatment FDG PET-CT findings with an SUVmax greater than 5.0 should undergo close evaluation for possible residual or recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…HNSCC is a heterogeneous group of cancers that caused by squamous cell abnormalities 19 . The longtime survival rate of HNSCC remains poor due to the high rate of recurrence and distant metastasis 20 . It has been suggested that metabolic reprogramming is a cancer hallmark, and abnormal fatty acid metabolism is related to the malignant phenotype in HNSCC, including chemoresistance, relapse and metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC is a heterogeneous group of cancers that caused by squamous cell abnormalities 19 . The longtime survival rate of HNSCC remains poor due to the high rate of recurrence and distant metastasis 20 . It has been suggested that metabolic reprogramming is a cancer hallmark, and abnormal fatty acid metabolism is related to the malignant phenotype in HNSCC, including chemoresistance, relapse and metastasis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This is usually followed by routine clinical surveillance (history, physical examination, and endoscopic assessment) with or without subsequent surveillance imaging . The prognostic value of post-RT PET/CT has been demonstrated in multiple studies, with excellent negative predictive value in the definitive RT and postoperative RT (after a curative surgery) settings . Clear and concise results must be communicated to the oncology team that is treating the patient for this prognostic value to translate into improved patient care in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…14 Alternatively, several studies have reported the benefits of PET/CT imaging in patients with head and neck cancer. Specifically, the use of PET/CT surveillance can spare patients unnecessary neck dissections, 15,16 and PET/CT has higher diagnostic performance in the detection of disease recurrence compared with CT. [17][18][19][20][21] In addition, 2 prior studies, one from the United Kingdom and one from Australia, demonstrated that PET/CT surveillance can reduce health care costs by decreasing the need for radical neck dissections and by stratifying disease response, which allowed for fewer follow-up visits. 16,22 Longterm benefits of posttreatment imaging also have been reported, with adherence to surveillance imaging found to be an independent predictor of survival 5 to 10 years after the completion of therapy.…”
Section: Discussionmentioning
confidence: 99%